Advancing Safety through Collaboration: Developing Public Health Education in Research and Laboratory Safety for Campus, Government, and Industry - Weiderman, Rachael (My University, 2025)
Research and laboratory program outcomes reflect institutional safety initiatives and safety culture. The Applied Practice Experience, “Advancing Safety through Collaboration: Developing Public Health Education in Research and Laboratory Safety for Campus, Government, and Industry,” identified safety outcomes by analyzing reported incidents in research and laboratory environments, designing and implementing data-informed biannual collaborative education and training events, and proposing long-term, sustainable, tiered curriculum in research and laboratory safety for the campus community, government, and industry professionals. Through interdisciplinary and multisectoral collaboration, Kansas State University has integrated safety principles into institutional frameworks, mitigating risks, fostering professional development, and strengthening research integrity. The findings and methodologies outlined in this report may serve as a model for academic institutions to enhance their safety training programs and promote improved risk reduction through proactive institutional safety culture.
Keywords: Safety; Education; Laboratory safety; Research safety; Compliance; Risk mitigation; Safety training; Professional development